Characterization of solid fuel by Palm Oil Mill Effluent (POME) - Mohd Shah, Muhammad Najmi (2019)
Palm oil industry is recognized as one the major agriculture contributions to the abundant production of oil palm solid wastes. Hence, this study is aimed at investigating the solid fuel characterization of Palm Oil Mill Effluent (POME) using Thermogravimetric analysis (TGA). The heating value (HHV), ultimate and proximate analysis was determined using standard ASTM techniques. Consequently, the thermal decomposition behaviour of the fuel was determined by heating the sample from 50°C to 900°C in a thermogravimetric analyser (TGA) at 10°C per min heating rate. The ultimate and proximate analysis revealed that POME powder contains low moisture content, ash content and high fixed carbon, volatile matter content while the HHV was 17.57 MJ/kg. In addition, TGA results indicated thermal decomposition of the fuel occurs in four stages. Devitalization commenced at 206°C with a peak devitalization temperature (Tmax) of 325°C resulting in 70% weight loss